EVALUATION OF THE ANTIOXIDANT EFFECTS OF ZIZIPHUS MAURITIANA LAM. LEAF EXTRACTS AGAINST CHRONIC ETHANOL-INDUCED HEPATOTOXICITY IN RAT LIVER - Dahiru, D.; Obidoa, O. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Chronic alcohol ingestion is known to increase the generation of reactive oxygen species (ROS), thereby leading to liver damage. Antioxidant enzymes act individually or in combination to reduce or counter the effect of these ROS. Chronic administration of alcohol at (40% v/v, 1ml/100g), for 6 weeks showed a significant (p<0.05) elevated levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total bilirubin (TB). There was also a significant (p<0.05) decreased levels of catalase, glutathione peroxidase, glutathione reductase and superoxide dismutase compared to control rats. Pre-treatment of rats with 200, 400 mg/kg body weight of aqueous leaf extract of Ziziphus mauritiana or 100 mg/kg silymarin resulted in a significant (p<0.05) decreased levels of ALT, AST, ALP, and TB with levels of catalase, glutathione peroxidase, glutathione reductase and superoxide dismutase showing a significant (p<0.05) increase compared to group administered alcohol only. Histopathology of rat liver administered with alcohol only resulted in severe necrosis, mononuclear cell aggregation and fatty degeneration in the central and mid zonal areas which was a characteristic of a damaged liver. Pre-treatment with the aqueous extract of Ziziphus mauritiana or silymarin reduced the morphological changes that are associated with chronic alcohol administration. The presence of tannins, saponins and phenolic compounds observed in the plant extract could be responsible for the observed effects of decreasing the levels of injured tissue marker and lipid peroxidation.